Environmental policy and growth when inputs are differentiated in pollution intensity - Francesco Ricci (Fondazione Eni Enrico Mattei (FEEM), 2002)
Environmental policy affects the distribution of market shares if intermediate goods are differentiated in pollution intensity. When innovations are environmental friendly, a tax on emissions skews demand towards new goods, which are the most productive. In this case along a balanced growth path the tax has to increase to keep the market shares of goods of different vintages constant. An increase in the burden of taxation lowers output on impact but, comparing balanced growth paths, we find that it spurs innovation. Through this channel environmental policy may increase the growth rate of the economy.
Keywords: O41; Q28; H32; O30; 330; Endogenous growth; environmental policy; induced technological change; Umweltpolitik; Ökosteuer; Technischer Fortschritt; Wirtschaftswachstum; Neue Wachstumstheorie; Öko-Produkt; Theorie